2019
DOI: 10.3390/w11020202
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors Affecting Water Access in Rural Areas of Low and Middle Income Countries

Abstract: Worldwide, 844 million people still lack access to basic drinking water, especially in the rural areas of low and middle income countries. However, considerable progress has been made in recent years due to work on the Millennium Development Goals and Sustainable Development Goals. Nevertheless, countries’ national characteristics have often impacted on this progress. This paper analyzes whether specific socioeconomic factors affect access to improved water sources in the rural areas of developing countries. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 20 publications
7
27
0
Order By: Relevance
“…The conditions that people live in affect their access to clean water and proper sanitation. Despite the variable contexts in different countries, the common predictors of access to clean water and sanitation are income, education and geographical location [ 9 , 10 , 11 , 12 , 13 , 14 ]. The presence of a female head in an African household was associated with better access to clean water as women played a traditional role in fetching water for the household [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conditions that people live in affect their access to clean water and proper sanitation. Despite the variable contexts in different countries, the common predictors of access to clean water and sanitation are income, education and geographical location [ 9 , 10 , 11 , 12 , 13 , 14 ]. The presence of a female head in an African household was associated with better access to clean water as women played a traditional role in fetching water for the household [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These interrelationships can also be seen at the macro-level. For instance, a study on the specific socioeconomic factors that affect access to improved water sources in the rural areas of developing countries, found that female primary school completion rate (and other variables, including gross national income and agriculture) were related to water access, demonstrating the complex interrelationship between access to improved water supplies, and gender [5].While some research has been conducted on the drivers of privately owned, small piped-water schemes in the Asia and the Pacific, there is little evidence specifically focused on Cambodia. In Cambodia, small-scale piped-water systems delivered by enterprises are connected directly to people's houses or near their house, and fitted with a water meter.…”
mentioning
confidence: 99%
“…These interrelationships can also be seen at the macro-level. For instance, a study on the specific socioeconomic factors that affect access to improved water sources in the rural areas of developing countries, found that female primary school completion rate (and other variables, including gross national income and agriculture) were related to water access, demonstrating the complex interrelationship between access to improved water supplies, and gender [5].…”
mentioning
confidence: 99%
“…Similarly, lower-income households in Haiti have high susceptibility factors of 2.4 in contracting enteric diseases than high-income household children; 41% of water supply sources in Bangladesh is contaminated with E. coli and 56% of the top 20% in India has access to treated water compared to 6% of the bottom 20% ( World Bank Group, 2017b ). Developing nations have been ravaged with high death rates due to the use of contaminated water from complications from enteric diseases, with a larger percentage of these populations from rural dwellers ( Gomez et al, 2019 ). The socioeconomic imbalance of water supply and sanitation have rendered the low-income earners to wait for options provided by the government, which sometimes are irregular.…”
Section: Socioeconomic Inequality Due To Virus-associated Water Pollumentioning
confidence: 99%